2014
DOI: 10.1080/21642583.2014.956265
|View full text |Cite
|
Sign up to set email alerts
|

Random forests: from early developments to recent advancements

Abstract: Ensemble classification is a data mining approach that utilizes a number of classifiers that work together in order to identify the class label for unlabeled instances. Random forest (RF) is an ensemble classification approach that has proved its high accuracy and superiority. With one common goal in mind, RF has recently received considerable attention from the research community to further boost its performance. In this paper, we look at developments of RF from birth to present. The main aim is to describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
289
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 535 publications
(296 citation statements)
references
References 31 publications
1
289
0
6
Order By: Relevance
“…During the process of elimination, 10-fold cross validation was implemented to optimize the variable selection and to ascertain the standard RF is a collection of several decision trees where each tree is constructed independently with random samples (n) from the training data. Random samples were drawn with the replacement from the training data using a bootstrap aggregating (bagging) method, which was found to be a more robust method for obtaining a stable model and helped to avoid overfitting [33]. Usually, 64% of training data is selected as in-bag data, and the remaining 36% were referred to as out-of-bag (OOB) data.…”
Section: Introductionmentioning
confidence: 99%
“…During the process of elimination, 10-fold cross validation was implemented to optimize the variable selection and to ascertain the standard RF is a collection of several decision trees where each tree is constructed independently with random samples (n) from the training data. Random samples were drawn with the replacement from the training data using a bootstrap aggregating (bagging) method, which was found to be a more robust method for obtaining a stable model and helped to avoid overfitting [33]. Usually, 64% of training data is selected as in-bag data, and the remaining 36% were referred to as out-of-bag (OOB) data.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive experimental study has shown the potential of this approach. For more information about these techniques, the reader is referred to the survey paper in [13]. In a more recent work, diversification using weighted random subspacing was proposed in [12].…”
Section: Related Workmentioning
confidence: 99%
“…Combining Breiman's bagging sampling method (1996a) and the random selection of features introduced individually by Ho (1998) and Amit and Geman (1997), it perform excellently for linear and nonlinear prediction by keeping the balance between bias and variance. Additionally, the advantages of RF include (Fawagreh et al, 2014): 1. Accuracy of classification is very high 2.…”
Section: Random Forestsmentioning
confidence: 99%